Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/healthcare11081095
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of COVID-19 on Heart Rate Variability: A Systematic Review of Observational Studies

Abstract: Coronavirus disease 2019 (COVID-19) sequelae (or long COVID) has become a clinically significant concern. Several studies have reported the relationship between heart rate variability (HRV) parameters and COVID-19. This review investigates the long-term association between COVID-19 and HRV parameters. Four electronic databases were searched up to 29 July 2022. We included observational studies comparing HRV parameters (measurement durations: 1 min or more) in participants with and without a history of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 69 publications
2
4
0
Order By: Relevance
“…There was heterogeneity across measures of autonomic function in long COVID cases. On average, HR recovered more rapidly in controls than in long COVID cases, in line with previous work (Asarcikli et al., 2022 ; Contreras et al., 2023 ; Dani et al., 2021 ; Marques et al., 2022 ; Suh et al., 2023 ). During the lying to standing maneuver, one individual met the clinical criteria for orthostatic hypotension and a further two met the criteria for POTS (Raj et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…There was heterogeneity across measures of autonomic function in long COVID cases. On average, HR recovered more rapidly in controls than in long COVID cases, in line with previous work (Asarcikli et al., 2022 ; Contreras et al., 2023 ; Dani et al., 2021 ; Marques et al., 2022 ; Suh et al., 2023 ). During the lying to standing maneuver, one individual met the clinical criteria for orthostatic hypotension and a further two met the criteria for POTS (Raj et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Their results revealed a reduction in global HRV, increased sympathetic modulation influence and a decrease in parasympathetic modulation in long COVID [69]. A recent systematic review confirmed a decreased parasympathetic activity, although the authors suggested standard deviation of all NN intervals as a reference parameter [70]. This seems comparable to our HRV data, suggesting long COVID patients tend to have a sympathetic profile with a very low parasympathetic component.…”
Section: Discussionsupporting
confidence: 84%
“…Long COVID-19 refers to the signs and symptoms that continue or appear after the acute COVID-19 stage [25][26][27],most of our study population are belong to this. Research has found that the mechanism of long COVID-19 may be related to autonomic dysfunction [28].In the two meta-analyses published in 2022 on COVID-19 and HRV, a total of 31 articles were included [29,30]. The vast majority of the 31 articles compared HRV parameters between acute phase patients and healthy control groups, with different methods for comparing HRV parameters, including bedside electrocardiogram monitoring, wearable devices, conventional 12 lead electrocardiogram, and a small number of articles also using 24 h Holter ECG.…”
Section: Discussionmentioning
confidence: 99%